A comunicação no processo de internacionalização de empresas: um estudo de caso Latam - Sampaio, Amanda Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Organizations, during the process of merger and acquisition of companies, go through several economic and, mainly, cultural challenges throughout their internationalization, often resulting from the relationships between different people, cultures, languages, values, and may be in charge of communication identify and improve these processes within organizations. This course conclusion paper seeks to verify the role of communication in the internationalization process of companies, through the bias of organizational culture and organizational identity. This work carried out an exploratory study in relation to the company Latam. Regarding the methodology, a bibliographic research, documentary analysis, analysis of two audiovisual campaigns and an in-depth, semi-structured interview with a former employee of the company were carried out. We were able to verify from this work that, in the organizational environment in which two or more cultures interact with each other, there are several conflicts between individuals, and it is the role of communication to be present during this process, to build and reproduce the new culture and identity that arise.

As organizações, durante o processo de fusão e aquisição de empresas, passam por diversos desafios econômicos e, principalmente, culturais ao longo de sua internacionalização, muitas vezes decorrentes das relações entre diferentes pessoas, culturas, idiomas, valores, podendo ficar a cargo da comunicação identificar e melhorar esses processos dentro das organizações. Este trabalho de conclusão de curso busca verificar o papel da comunicação no processo de internacionalização de empresas, através do viés da cultura organizacional e da identidade organizacional. Este trabalho realizou um estudo exploratório em relação a empresa Latam. Em relação à metodologia, foram realizadas uma pesquisa bibliográfica, a análise documental, a análise de duas campanhas audiovisuais e uma entrevista em profundidade, semi-estruturada com uma ex-funcionária da empresa. Conseguimos aferir deste trabalho que, no ambiente organizacional em que duas ou mais culturas interagem entre si, há diversos conflitos entre os indivíduos, e é papel da comunicação estar presente durante esse processo, para construir e reproduzir a nova cultura e identidade que surgem.
Communication in the internationalization process of comapanies: a Latam case study
Keywords: Latam airlines; Organizational communication; Internalization of companies; Organizational culture; Organizational identity; Comunicação organizacional; Comunicação na administração; Internacionalização de empresas; Relações internacionais; Cultura organizacional; Identidade organizacional